SOSOK UMAR BIN KHAṬṬAB DAN LATAR BELAKANG LAHIRNYA RISALAH AL-QAḌĀ - La Aludin La Daa (IAIN Ambon, 2018)
One of the Muslim caliphs was Umar bin Khattab. In his time, judicial power began to be separated from the executive power. Even the governance of the judiciary has been set up, among others by imprisoning and appointing a number of judges to resolve disputes between members of the community. One form of coaching by the Caliph Umar bin Khaṭṭab to the judges in performing judicial duties is to send letters containing instructions and guidelines to the judges. One of the judges who had been sent a letter related to the administration of justice was Abu Musa Al-Ash'ari who served as a judge in Basra. The letter is known as the message of al-Qaḍā, which is in relation to the existence and position of the judiciary; court decisions must be exercised, principle of objectivity, proof / oath, peace, review, basis / source of law and interpretation of law, witness credibility.